Comparison of 18F-T807 and 18F-THK5117 PET in a Mouse Model of Tau Pathology - Brendel, Matthias; Yousefi, Behrooz H.; Blume, Tanja; Herz, Michael; Focke, Carola; Deussing, Maximilian; Peters, Finn; Lindner, Simon; von Ungern-Sternberg, Barbara; Drzezga, Alexander; Bartenstein, Peter; Haass, Christian; et al. (Frontiers in Aging Neuroscience, 2018)
Positron-emission-tomography (PET) imaging of tau pathology has facilitated development of anti-tau therapies. While members of the arylquinoline and pyridoindole families have been the most frequently used tau radioligands so far, analyses of their comparative performance in vivo are scantly documented. Here, we conducted a head-to-head PET comparison of the arylquinoline 18FT807 and the pyridoindole 18FTHK5117 PET in a mouse model of tau pathology. PET recordings were obtained in groups of (N=5-7) P301S and wild-type (WT) mice at six and nine months of age. Volume-of-interest based analysis (standard-uptake-value ratio, SUVR) was used to calculate effect sizes (Cohen’s d) for each tracer and age. Statistical parametric mapping (SPM) was used to assess regional similarity (dice coefficient) of tracer binding alterations for the two tracers. Immunohistochemistry staining of neurofibrillary tangles was performed for validation ex vivo. Significantly elevated 18F-T807 binding in the brainstem of P301S mice was already evident at six months (+14%, p<0.01, d=1.64), and increased further at nine months (+23%, p<0.001, d=2.70). 18F-THK5117 indicated weaker increases and effect sizes at six months (+5%, p<0.05, d=1.07) and nine months (+10%, p<0.001, d=1.49). Regional similarity of binding of the two tracers was high (71%) at nine months. 18F-T807 was more sensitive than 18F-THK5117 to tau pathology in this model, although both tracers present certain obstacles, which need to be considered in the design of longitudinal preclinical tau imaging studies.